Provenance and Petrographic Analysis of Paleogene Sandstones in the Bukit Tigapuluh Area, Jambi Subbasin, Indonesia - Daryono, Sapto Kis; Idarwati, Idarwati (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
The study investigates the provenance of Paleogene sandstone deposits from the Lemat Formation in the Lubuk Lawas and Lubuk Bernai sections of the Bukit Tigapuluh area, Jambi Subbasin, South Sumatra Basin, Indonesia. The research aims to elucidate the formation history and stratigraphic evolution of these sedimentary rocks through detailed petrographic analysis. Twenty-two rock samples were analyzed to classify the sandstones and determine their source rock types and tectonic settings. The results indicate that the sandstones are primarily classified as Lithic Arkose, Arkosic Subarkose, Feldspathic Litharenite, Silty Claystone, Sublitharenite, and Subarkosic Wacke. The provenance analysis suggests that these sandstones originated from a tectonic setting of a recycled orogenic zone, comprising quartzose recycled, transitional recycled, and mixed sources, indicating a combination of primary and recycled orogenic materials. Paleocurrent analysis from sedimentary structures in the Lubuk Bernai area suggests deposition directions from the southwest and southeast. This study provides significant insights into the paleogeography and tectonic evolution of the Lemat Formation within the Jambi Subbasin. Further research should focus on integrating geochemical data to refine the understanding of sedimentary provenance and tectonic implications.